'It seems like you're going around in circles': recurrent biographical disruption constructed through the past, present and anticipated future in the narratives of young adults with inflammatory bowel disease. Issue 5 (20th April 2017) - Saunders, Benjamin
Abstract: Biographical disruption and related concepts continue to be widely drawn upon in explaining how individuals experience chronic illness. Through in‐depth examination of the narrative experiences of two young adults with inflammatory bowel disease (IBD), this article aims to contribute to the continuing theoretical elaboration of biographical disruption, and in turn offer new insights into how young adults experience this condition. The cases are analysed from an interaction‐based, constructionist perspective, through which it is argued that the relapse‐remission nature of IBD can give rise to a particular form of recurrent biographical disruption, constructed in narrative through a complex configuration of past, present and anticipated future experiences. The two young adults are found to give different meaning to this recurrent disruption in terms of its significance and consequences – whilst Samuel represents an ongoing cycle of profound disruption and biographical reinstatement, Edith normalises the cycle of disruption and its role in her ongoing biography. Therefore, moving beyond the notion of 'normal illness' observed in previous research literature, the concept of 'normal recurrent disruption' is proposed. Finally, it is argued that this recurrent biographical disruption may be experienced particularly severely in young adulthood owing to the unique pressures and expectations of this lifestage.